2016
DOI: 10.1371/journal.pone.0167401
|View full text |Cite
|
Sign up to set email alerts
|

β-Asarone Rescues Pb-Induced Impairments of Spatial Memory and Synaptogenesis in Rats

Abstract: Chronic lead (Pb) exposure causes cognitive deficits. This study aimed to explore the neuroprotective effect and mechanism of β-asarone, an active component from Chinese Herbs Acorus tatarinowii Schott, to alleviate impairments of spatial memory and synaptogenesis in Pb-exposed rats. Both Sprague-Dawley developmental rat pups and adult rats were used in the study. Developmental rat pups were exposed to Pb throughout the lactation period and β-asarone (10, 40mg kg-1, respectively) was given intraperitoneally fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…After reading the remaining 285 full-text articles, 228 studies were excluded for at least one of following reasons: (1) not an animal study; (2) the article was not a research about cognitive impairment; (3) the study did not access the effects of AGA or active component on the animal model of cognitive impairment; (4) EAAGA was not used as a monotherapy; and (5) lack of control group. Ultimately, 34 eligible articles [ 5 , 6 , 10 , 11 , 17 – 46 ] were selected ( Figure 1 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the remaining 285 full-text articles, 228 studies were excluded for at least one of following reasons: (1) not an animal study; (2) the article was not a research about cognitive impairment; (3) the study did not access the effects of AGA or active component on the animal model of cognitive impairment; (4) EAAGA was not used as a monotherapy; and (5) lack of control group. Ultimately, 34 eligible articles [ 5 , 6 , 10 , 11 , 17 – 46 ] were selected ( Figure 1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The weight of SD rats ranged from 200 g to 650 g, the weight of Wistar rats used ranged from 30 g to 250 g, and the weight of mice ranged from 17 g to 50 g. Twenty-two studies used male rodents, 1 study used female rodents, 5 study used both female and male rodents, and the remaining 6 studies did not provide gender details. Sodium pentobarbital was used to induce anesthesia in 8 studies, and chloral hydrate was used in 2 studies [ 20 , 21 ], 1 study [ 41 ] used phenytoin sodium, 1 study [ 17 ] used CO 2 , and 1 study [ 10 ] used isoflurane, while the remaining 21 studies did not report the type of anesthetics. Cognitive impairment models were induced by lead [ 17 ], noise stress [ 18 ], LPS [ 19 ], amyloid beta 1-42 [ 11 , 21 , 26 , 28 , 29 , 37 , 41 , 46 ], D-gal plus AlCl 3 [ 22 ], scopolamine [ 5 , 24 , 30 , 34 – 36 , 42 , 45 ], ethanol [ 5 , 32 , 34 – 36 ], sodium nitrite [ 5 , 32 ], corticosterone [ 23 ], Ibotenic acid [ 25 ], chronic restraint stress [ 31 ], pentobarbital sodium [ 32 ], D-galactose [ 33 , 38 ], AlCl 3 [ 40 ] , streptozotocin (STZ) [ 43 ], pent ylenetet razol (PTZ) [ 44 ], and NaNO 2 [ 34 – 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…β-asarone is an active oriental herb component which reverts damage inflicted by Pb over spatial memory, possibly through synaptogenesis (Yang et al, 2016 ). Developmental rat pups were exposed to Pb throughout lactation period and β-asarone (10, 40 mg/kg, respectively) was administered intraperitoneally from postnatal day 14–21.…”
Section: Preventive and Therapeutic Treatment Schemes To Prevent The mentioning
confidence: 99%
“…The above mentioned results suggest neuroprotective properties of β-asarone against Pb-induced memory impairments and an effect possibly related to the regulation of synaptogenesis, mediated via Arc/Arg3.1 and Wnt pathway. Traditional use and clinical reports showed that β-asarone is effective for the treatment of learning and memory deficits; therefore, it is likely to manage memory impairment following chronic Pb exposure (Yang et al, 2016 ).…”
Section: Preventive and Therapeutic Treatment Schemes To Prevent The mentioning
confidence: 99%
“…Moreover, β-asarone increased the expression of neurotrophin such as brain-derived neurotrophic factor (BDNF), glial cellderived neurotrophic factor, and ciliary neurotrophic factor in RSC96 cells [19]. β-asarone treatment also improved the spatial learning and memory in Aβ (1-42)-induced memory-impaired rats [20]; in transgenic model of Alzheimer's disease such as Senescence-accelerated prone-8 (SAMP-8) mice [21]; and AβPP/PS1 double transgenic mice [22,23],also in chronic exogenous corticosterone-induced memoryimpaired rats [24,25]. Then, we describe that the attribution of pathogenesis of MHE is upregulation of DA, followed by the production of TNFα from neurons, leading to the disruption of synaptic formation, which was diminished by βASA treatment.…”
Section: Introductionmentioning
confidence: 98%